EFFECT OF ETCHING METHODS IN METALLOGRAPHIC STUDIES OF DUPLEX STAINLESS STEEL 2205 - Kisasoz, A.; Karaaslan, A.; Bayrak, Y. (SPRINGER, 2017)
Three different etching methods are used to uncover the ferrite-austenite structure and precipitates of secondary phases in stainless steel 22.5% Cr - 5.4% Ni - 3% Mo - 1.3% Mn. The structure is studied under a light microscope. The chemical etching is conducted in a glycerol solution of HNO3, HCl and HF; the electrochemical etching is conducted in solutions of KOH and NaOH.
Keywords: duplex stainless steel; secondary phases; etching; light microscopy; MECHANICAL-PROPERTIES; CORROSION-RESISTANCE; AGING TREATMENTS; HEAT-TREATMENT; MICROSTRUCTURE; Metallurgy & Metallurgical Engineering